THE IMPACT OF ARTIFICIAL INTELLIGENCE ON MODERN EDUCATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the transformative impact of Artificial Intelligence (AI) on modern education. It highlights how AI technologies are reshaping teaching methods, personalizing learning experiences, and improving student assessment. The paper also discusses the challenges of AI integration, such as ethical concerns and the digital divide. Overall, the study emphasizes the potential of AI to enhance educational quality and accessibility in the 21st century.